Paramedial and Bol* Abel-Grassmann Groupoids - Shah, M.; Ahmad, I. (The Nucleus, 2015)
We introduce a new class of groupoids which we name Bol*-groupoids. This in turn gives another new class of AG-groupoids that we call Bol*-AG-groupoids. We also enlist two new classes of AG-groupoids namely paramedial AG-groupoids and AG-groupoid-semigroups. The latter is also an interesting new class of semigroups. We discuss some basic properties of these newly introduced classes and provide various finite examples to show their existence.